Medicine, miracle and magic in New Testament times - Kee, Howard Clark (Cambridge, NY Cambridge UP, 1986)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Miracles -- criticism, interpretation, etc; Medicine in the Bible